TINJAUAN SPT PPH WAJIB PAJAK BADAN ATAS PERALIHAN TARIF UMUM PASAL 31E PT. K OLEH BEN & CO. CONSULTING - Melinda Angraeni (2021)
Corporate Income Tax is a state tax that is subject to any economic additions received by taxpayers from a business entity both from within and outside the country. The transition in tax rate in tax rates in a company causes the company to enter a transition period which requires the company to make adjustments to the recording or bookkeeping and recalculation of the corporate income tax payable in one tax year in accordance with tax provisions which will then be applied in the company and based on the regulation of the Minister of Finance PT. K does not need to pay PPh Article 25 in the first Tax year as a New Taxpayer. The purpose of the preparation of this Final Project is to review further about the things that must be done or faced by a company or entity during the tariff transition period. With the hope that this review can provide information and serve as a medium in adding knowledge related to taxes, especially when a business undergoes a transition as described above which can be useful for the wider party.